Le « Scholarship of Teaching and Learning » (SoTL). Proposition d'un cadre pour l'accompagnement des enseignants par les conseillers pédagogiques - Sandrine Biémar; Amaury Daele; Déborah Malengrez; Laurence Oger
This paper presents a review of the literature on Scholarship of Teaching and Learning (SoTL) of teachers in higher education and how faculty developers support building of their capacities in the field. The authors suggest a reflective framework encompassing the different phases of SoTL. It comprises the different conceptions teachers hold regarding their own professional development and the actions carried out by faculty developers to support them throughout the process. This framework is illustrated with examples from a Belgian Higher Education institution and a Swiss University.